Camel Milk Targeting Insulin Receptor—Toward Understanding the Antidiabetic Effects of Camel Milk - Anwar, Irfa; Khan, Farheen Badrealam; Maqsood, Sajid; Ayoub, Mohammed Akli (Frontiers in Nutrition, 2022)
Camel milk (CM) is known for its beneficial virtues in the human diet and health. This includes its antidiabetic properties demonstrated in many in vitro and in vivo studies. Nevertheless, the scientific rationale behind the molecular and cellular basis of such beneficial effects and the exact antidiabetic agent(s)/mechanism(s) are still elusive. In this review, we focused on the recent advances supporting the targeting of insulin receptor (IR) by CM components. Indeed, our recent work reported that CM proteins and derived peptides pharmacologically target IR in vitro leading to its activation and potentiation of insulin-mediated responses. The review describes the experimental approaches used to investigate the effects of CM on IR in vitro based on the fractionation of CM whey proteins to purify functional proteins and their hydrolysis by gastric proteases to generate bioactive peptides. In addition, we illustrated our cellular and molecular model consisting of studying the functional activity of CM fractions on IR and its downstream signalling pathways in the hepatocarcinoma (HepG2) and the human embryonic kidney (HEK293) cells using the bioluminescence resonance energy transfer (BRET), phosphorylation, and glucose uptake assays. Overall, our work demonstrated for the first time that CM lactoferrin and CM-derived bioactive peptides positively modulate IR and its related signaling pathways in HepG2 and HEK293 cells. As a conclusion, the pharmacological targeting of IR by CM sheds more light on the antidiabetic properties of CM by providing its molecular basis that may constitute a solid rationale for the development of new generation of antidiabetic tools from CM-derived proteins and peptides and the utilization of CM in the management of diabetes. The sequencing and the synthesis of the potent bioactive CM peptides may open promising perspectives for their application as antidiabetic agents.